Genetic Analysis of Tropical Midaltitude‐Adapted Maize Populations under Stress and Nonstress Conditions. Issue 4 (7th June 2018) - Makumbi, Dan; Assanga, Silvano; Diallo, Alpha; Magorokosho, Cosmos; Asea, Godfrey; Worku, Mosisa; Bänziger, Marianne
Abstract : Maize ( Zea mays L.) yield in sub‐Saharan Africa (SSA) is low because of both abiotic and biotic constraints, and limited availability or use of improved seed in some areas. This study was conducted (i) to estimate combining ability and heterosis among seven stress‐tolerant populations, and (ii) to assess diversity among the populations and the relationship between diversity and heterosis. Twenty‐one hybrids developed from diallel crosses of seven populations, parents, and two checks were evaluated in 10 optimal and 11 stressed environments (drought, low N, and random stress) in Kenya, Ethiopia, Uganda, and Zimbabwe for 2 yr. Analysis II of Gardner and Eberhart showed that variety and heterosis were significant for grain yield (GY) under optimal and managed stress, and across environments. Heterosis accounted for most of the variation for GY among populations under optimal conditions (67%) and drought stress (53%), which suggested the importance of dominance in inheritance of GY under these conditions. Genetic distance (GD) among populations ranged from 0.328 to 0.477 (mean = 0.404). The correlation between GD and heterosis was low ( r = 0.14–0.40) in all environments. The simple sequence repeat (SSR) marker‐based and GY‐based clustering of parental populations showed similar patterns, with three populations distinct from the rest, suggesting significant differentiation of allelic variation in these three populations. The SSR‐based diversity and phenotypic analysis results should be useful in defining breeding strategies and maintaining heterotic patterns among these populations.